Need-supportive teaching and student engagement in the classroom: Comparing the additive, synergistic, and global contributions. (February 2021) - Olivier, Elizabeth; Galand, Benoit; Morin, Alexandre J.S.; Hospel, Virginie
Abstract: This study contrasts three hypotheses to determine the best configuration of teacher need-supporting practices (autonomy support, structure, and involvement) in terms of classroom-levels of behavioral, emotional, and cognitive engagement. Multilevel analyses were conducted among a sample of 1193 8th grade students nested in 57 math classrooms. Results failed to support the additive hypothesis (H1), which anticipated that all three practices would be associated with classroom-levels of engagement when jointly considered. Results also failed to support the synergistic hypothesis (H2), which predicted that the greatest benefits would emerge in classrooms characterized by a high level of two or three practices. Finally, results supported the global hypothesis (H3), which anticipated that the global level taken across the three practices—captured by a global factor—would provide optimal support to classroom-levels of engagement. Specific factors representing the imbalance in autonomy support, structure, and involvement also contributed to some aspects of classroom-levels of engagement. Highlights: The study relies on CFA, bifactor-CFA and multilevel modeling. It contrasts the additive, synergistic, and global contribution of SDT-based teaching practices. Results did not support the additive contribution of teaching practices to student engagement. Results did not support the synergistic contribution of teaching practices to student engagement. Results supported the global contribution of teaching practices to student engagement.